A flexible optoacoustic blood ‘stethoscope’ for noninvasive multiparametric cardiovascular monitoring - Jin, Haoran; Zheng, Zesheng; Cui, Zequn; Jiang, Ying; Chen, Geng; Li, Wenlong; Wang, Zhimin; Wang, Jilei; Yang, Chuanshi; Song, Weitao; Chen, Xiaodong; Zheng, Yuanjin (Nature communications, 2023)
Quantitative and multiparametric blood analysis is of great clinical importance in cardiovascular disease diagnosis. Although there are various methods to extract blood information, they often require invasive procedures, lack continuity, involve bulky instruments, or have complicated testing procedures. Flexible sensors can realize on-skin assessment of several vital signals, but generally exhibit limited function to monitor blood characteristics. Here, we report a flexible optoacoustic blood ‘stethoscope’ for noninvasive, multiparametric, and continuous cardiovascular monitoring, without requiring complicated procedures. The optoacoustic blood ‘stethoscope’ features the light delivery elements to illuminate blood and the piezoelectric acoustic elements to capture light-induced acoustic waves. We show that the optoacoustic blood ‘stethoscope’ can adhere to the skin for continuous and non-invasive in-situ monitoring of multiple cardiovascular biomarkers, including hypoxia, intravascular exogenous agent concentration decay, and hemodynamics, which can be further visualized with a tailored 3D algorithm. Demonstrations on both in-vivo animal trials and human subjects highlight the optoacoustic blood ‘stethoscope’‘s potential for cardiovascular disease diagnosis and prediction. Cardiovascular disease diagnosis can be invasive and complex. Here, the authors present a flexible optoacoustic blood ‘stethoscope’ that noninvasively and continuously monitors cardiovascular health.